Enhancing Early Grade Learners' Critical Thinking Skills for Self-Reliance - Ekeh, Martin Chukwudi; Venketsamy, Roy (Profesi Pendidikan Dasar, 2023)
Although most Nigerian schools are yet to meet the demands characterising 21st-century learners, they must be equipped to fit into a global society constantly striving toward self-reliance. Therefore, there is a need for Nigerian teachers to adopt 21st-century learning skills, such as the critical thinking skills learning approach, to develop self-reliance in early grades. The research context was in pre-primary and primary schools in the Owerri Education Zone of Imo State, Nigeria. The authors adopted a qualitative research methodology employing Participatory Action Research (PAR) as the design. Data were collected using semi-structured interview questions. The data were then analyzed using thematic data analysis procedures. The study's findings revealed that the critical thinking skills learning approach developed self-reliance in early-grade learners. In conclusion, the authors recommended an adequate continuous professional development program for teachers to improve their knowledge of 21st-century learning pedagogy. Further research should be conducted using other aspects of 21st-century learning pedagogy to enhance self-reliance.